INTEGRASI PEMBELAJARAN BERBASIS BUDAYA DAN KEARIFAN LOKAL DALAM KURIKULUM MADRASAH IBTIDAIYAH: ANALISIS LITERATUR TENTANG MODEL DAN IMPLEMENTASINYA - Miskiyyah, Sylvia Zakiyyatul; Puspita, Putri Indah; Dewi, Tri Buana Tungga; Mu’izzah, Rodliyatul; Febriyanti, Anisa Auliya; Suttrisno, Suttrisno (STKIP Pesisir Selatan, 2025)
This study aims to analyze the methods and implementation of learning integration that focuses on culture and local wisdom of Bojonegoro in the curriculum of Madrasah Ibtidaiyah (MI). To achieve this goal, the method applied is library research with a descriptive qualitative approach. Data sources are taken from scientific journals, academic books, and policy documents related to the theme of local culture-based learning. The findings of this study indicate that the use of contextual learning models and culturally responsive teaching are effective methods for integrating local wisdom values ​​into the learning process. The implementation of this integration has a positive impact on student motivation in learning, character formation, and strengthening cultural identity. However, in the field there are still several challenges faced, such as limited learning resources and lack of training for teachers. The main innovation of this study lies in emphasizing the importance of cooperation between educational institutions, local governments, and communities in creating a sustainable culture-based learning environment in MI, especially in the Bojonegoro area.